PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, UKURAN DEWAN KOMISARIS, DAN LEVERAGE TERHADAP LUAS PENGUNGKAPAN GOOD CORPORATE GOVERNANCE (Studi Empiris Perusahaan Manufaktur di BEI Tahun 2008–2012) - Ridho, Nailun Ahmad; Sulistiani, Dwi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2014)
Title: [The Effect of Company Size, Profitability, Commissioner Board Size and Leverage on Widespread Disclosure of Good Corporate Governance: Empirical Study on Manufacturing Companies are Listed in IDX among Year 2008-2012]Corporate Governance is sets of rules that affect management to create a strong system and firm structure. This study was conducted to analyze the factors that affect the wider corporate governance disclosure in annual report on manufacturing companies in Indonesia Stock Exchange (IDX). This research is descriptive quantitative research. The data used are secondary data companies that listed on the Stock Exchange from the period 2008 to 2012. Factors tested in this research were firm size, profitability, board size, and leverage. Sampling methods used in this research was purposive sampling. The analysis technique is used multiple linear analysis methods for Hypothesis testing. The results of this study indicate that partially independent variables that significantly influence the broad disclosure of corporate governance is the profitability and leverage. Profitability variables have a significant effect because the companies with high profit companies have a responsibility to disclose more information even as the number of interested stakeholders. While the leverage effect is also significant because the company with high leverage levels will disclose more information to creditor’s necessity with the result that reduces the supervision’s cost. Whereas no effect was variable firm size and board size. The variable size of the company does not have a significant effect because the large-sized companies are more likely to have greater agency problems anyway, so it needs more stringent good corporate governance mechanism, especially in manufacturing companies with different levels of difficulty with other types of companies. While the board size variable is also not significant because the number of commissioners would effect to then many entries received by directors and will effect the decision of the board of directors. Independent variables can explain the widespread influence of corporate governance disclosure by 33.2% while the remaining 66.8% can be explained by factors beyond research.